1988
DOI: 10.1016/0020-7292(88)90131-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactic dehydrogenase and its isoenzymes in patients with ovarian dysgerminoma

Abstract: Lactic dehydrogenase (LDH) is a glycolytic enzyme that may be elevated in the serum of patients with gonadal and extragonadal germinomas. In this report, a case of unilateral ovarian pure dysgerminoma with remarkably elevated levels of serum LDH is presented. After complete excision of the tumor, serum LDH levels promptly returned to normal levels. Although an electrophoretic pattern of serum LDH isoenzymes was within normal limits pre-operatively, an increase in LDH-1 and 2 was found 1 week after operation. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
2
4
0
1
Order By: Relevance
“…It has been suggested that serum LDH levels and their isoenzyme pattern are useful tumor markers for diagnosis and post-therapy surveillance. 21 We therefore agree with the previous data 5, 22 that LDH has only a limited clinical use.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that serum LDH levels and their isoenzyme pattern are useful tumor markers for diagnosis and post-therapy surveillance. 21 We therefore agree with the previous data 5, 22 that LDH has only a limited clinical use.…”
Section: Discussionsupporting
confidence: 93%
“…The reported incidence is 0.42 per 1000 pregnancies mainly borderline tumors followed by epithelial tumors [14]. However, diagnosis of ovarian mass was late at 22 weeks of pregnancy as the mass may mimic luteoma of pregnancy and corpus luteum hematoma .The diagnosis was supported by elevated LDH which agreed with other authors [15]. To the best of our knowledge, no published studies to report the association between ovarian stimulating drugs and malignant germ-cell tumors in women with PCOS.…”
Section: Discussionsupporting
confidence: 81%
“…LDH was reported to be raised in malignant primary [17][18][19] and secondary [19] ovarian tumors, with no difference with regards to histological subtypes [18][19]. High LDH levels have been associated with ovarian and extragonadal dysgerminomas [20][21][22][23]. However, older studies did not report a significant association between LDH and ovarian tumors [24].…”
Section: Markermentioning
confidence: 99%